Innovative performance and firm size: a meta-regression analysis - Bachmann, Federico (2021)
The aim of this research is to determine factors related to observed heterogeneity in the empirical literature regarding the relationship between size and innovative performance at firm level. Based on a systematic review of international literature published between 1993 and 2017, a meta-regression analysis is carried out in order to evaluate publication bias in the empirical evidence. The results show a positive relationship between firm size and innovative performance, which is moderated by diverse factors. Among them, methodological choices of the authors prevail, linked to the operationalization of size and innovation. Signs of publication bias are detected, and partially explained by methodological choices.